Anti-stress Effects of Ginkgo biloba and Panax ginseng: a Comparative Study - Deepak Rai; Gitika Bhatia; Tuhinadri Sen; Gautam Palit (Elsevier, 2003)
ABSTRACT: Stress is a global menace fortified by the advancement of industrialization. Failure of stress management is due to lack of proper evaluation of anti-stress products. We explored the anti-stress potential of the Ginkgo biloba (G. biloba, 30 mg/kg, p.o.) and compared it with that of Panax ginseng (P. ginseng, 100 mg/kg, p.o.) against acute stress (AS) and chronic stress (CS) models in rats. Immediately after AS and CS, the rats were sacrificed, and adrenal glands and stomach were dissected out for weight determination and scoring of the ulcer index (UI), respectively, as well as changes in biochemical parameters like plasma glucose (GL), triglycerides (TG), cholesterol (CL), creatine kinase (CK), and serum corticosterone (CORT) were also estimated. AS significantly increased UI, adrenal gland weight (AGW), GL, CK activity, and CORT, whereas G. biloba significantly reduced them. P. ginseng significantly reverted GL and CK activity. In CS, a significant increase was found in the UI, AGW, CK activity, and CORT with a decrease in the level of CL and TG. G. biloba did not produce any significant effect on CS-induced alterations. P. ginseng reduced the UI, AGW, plasma GL, TG, CK activity, and CORT level significantly. From the above study, G. biloba is more effective in AS, whereas for CS, P. ginseng will be a better option. Hence these extracts possess significant anti-stress properties and can be used for the treatment of stress-induced disorders.